An interesting case of asymptomatic giant submandibular sialolithiasis: a case report - Mathew, Nitty; Asharaf, Amitha A.; Nayak, Prateek Pandurang (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Sialolithiasis is the most common disease of salivary glands. On the other hand, giant submandibular sialoliths or megaliths are quite rare. Our case report is of an unusually large submandibular sialolith called a giant sialolith as dimensions exceed 15 mm in size. Patient was asymptomatic on presentation and had preserved gland function. A firm mass was detected on the left floor of mouth and on transoral sialolithotomy a single large calculus of 40 mm, in greatest dimension, was removed in toto. Though submandibular gland sialoliths are generally asymptomatic in nature, giant calculi usually present with symptoms including pain and swelling of the involved gland caused by the accumulation of saliva, due to blockage of the lumen of Wharton’s duct by the calculus. This is a rare case report of an asymptomatic giant submandibular sialoithiasis, its diagnosis and management.